2022
DOI: 10.1016/j.bbi.2021.12.007
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike S1 subunit induces neuroinflammatory, microglial and behavioral sickness responses: Evidence of PAMP-like properties

Abstract: SARS-CoV-2 infection produces neuroinflammation as well as neurological, cognitive (i.e., brain fog), and neuropsychiatric symptoms (e.g., depression, anxiety), which can persist for an extended period (6 months) after resolution of the infection. The neuroimmune mechanism(s) that produces SARS-CoV-2-induced neuroinflammation has not been characterized. Proposed mechanisms include peripheral cytokine signaling to the brain and/or direct viral infection of the CNS. Here, we explore the novel hypothesis that a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
112
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 88 publications
8
112
2
1
Order By: Relevance
“…First, as already mentioned, Rhea et al [ 10 ] established that the cleaved S1 subunit can be transported from the olfactory epithelium to the hypothalamus, apparently by binding to ACE2. Second, Frank et al [ 14 ] showed that the S1 subunit, but not the S2 subunit, is sufficient to elicit neuroinflammation, including microglia activation and gene expression of multiple pro-inflammatory cytokines, as well as altered animal behavior reminiscent of neurological and cognitive symptoms in COVID-19 patients. Since microglia do not express ACE2 [ 14 ], these effects are likely mediated by binding of the S1 protein to pattern recognition receptors such as those of the toll-like receptors, especially TLR4 [ 14 ].…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…First, as already mentioned, Rhea et al [ 10 ] established that the cleaved S1 subunit can be transported from the olfactory epithelium to the hypothalamus, apparently by binding to ACE2. Second, Frank et al [ 14 ] showed that the S1 subunit, but not the S2 subunit, is sufficient to elicit neuroinflammation, including microglia activation and gene expression of multiple pro-inflammatory cytokines, as well as altered animal behavior reminiscent of neurological and cognitive symptoms in COVID-19 patients. Since microglia do not express ACE2 [ 14 ], these effects are likely mediated by binding of the S1 protein to pattern recognition receptors such as those of the toll-like receptors, especially TLR4 [ 14 ].…”
Section: To the Editormentioning
confidence: 99%
“…Second, Frank et al [ 14 ] showed that the S1 subunit, but not the S2 subunit, is sufficient to elicit neuroinflammation, including microglia activation and gene expression of multiple pro-inflammatory cytokines, as well as altered animal behavior reminiscent of neurological and cognitive symptoms in COVID-19 patients. Since microglia do not express ACE2 [ 14 ], these effects are likely mediated by binding of the S1 protein to pattern recognition receptors such as those of the toll-like receptors, especially TLR4 [ 14 ]. Accordingly, emerging evidence suggests that the cleaved S1 subunit travels along the ACE2-expressing nervus terminalis neurons and their axons into the brain, and the spike protein subunit 1 may then activate microglia by binding to TLR4, resulting in enhanced expression of pro-inflammatory cytokines such as IL1b and antigen-presenting molecules such as MHCII – molecules that are also upregulated in postmortem brains of COVID-19 patients.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…However, increasing evidence supports that TLRs might play a role during SARS-CoV-2 pathogenesis 112 . It has been shown that the surface proteins of SARS-CoV-2 could behave as a PAMP, thereby inducing the upregulation of inflammatory factors in the rodent model through TLR2 and TLR4 113 . Prophylactic administration of a TLR2 agonist showed a protective effect against SARS-CoV-2 infection and decreased virus transmission through the activation of the innate immune system 114 .…”
Section: Tlr2 As a Potential Sars-cov-2 Receptor In The Cnsmentioning
confidence: 99%